Health education for children: strategy to combat dengue (Research, Society and Development, 2021)
Introduction: Dengue is a disease with compulsory notification and a threat to population health. The main strategy for its prevention and control is education and social participation. Objective: To promote health education as a strategy for awareness and prevention of dengue. Methodology: It is an exploratory quali-quantitative approach study. In this study, we used health educational activities with elementary school children in a state school located in a region with high rates of the disease in Belo Horizonte (northeast region). The effectiveness of educational activities was assessed through using pre- and post-intervention questionnaires. Results: The post-test results showed a considerable increase in the assertiveness of the questions in more than 50% of the participants, reinforcing the success of the interventions. Discussion: Conducting continuing education in a creative way, using dynamic methodologies in the school environment, improves the absorption and dissemination of content by children, so increasing efficiency in combating dengue. Conclusion: The study reached the child audience in a playful way, effectively promoting knowledge and such a strategy proves to be important in the dialogue and family responsibility in combating emerging diseases.